Transcultural transferability of transient therapeutic communities: the living-learning experience workshops. Issue 1 (2nd December 2020) - Lees, Jan; Haigh, Rex; Bruschetta, Simone; Chatterji, Anando; Dominguez-Bailey, Veronica; Kelly, Sandra; Lombardo, Aldo; Parkhe, Shama; Pereira, Joāo G.; Rahimi, Yousuf; Rawlings, Barbara
Abstract : Purpose: This paper aims to describe a method of training for practitioners in democratic Therapeutic Communities (TCs) which has been used in several settings across the world over the past 25 years: the "Living-Learning Experience" (LLE) workshop. It goes on to consider the cross-cultural implications of the work. Design/methodology/approach: Drawing on the experience of running exactly the same programme in different countries and cultures, the paper examines the cross-cultural adaptability and describes necessary adaptations for local circumstances. It also contains original ethnographic research in UK and Italy; further study is planned for other countries. Findings: The workshops are readily transferable to different cultures and are appreciated for their democratic and relational way of working. Research limitations/implications: The ethnographic study examines the workshops in some depth, in UK and Italy, and could usefully be replicated in other countries. No quantitative, outcome or follow-up studies have yet been done, and this paper could contribute to the design of useful quantitative studies. Practical implications: The paper demonstrates that the LLE is a useful experiential learning tool in widely different settings. It could be developed in different ways, such as for developing relational practice or establishing therapeutic environments in different settings. Social implications: The workshops' acceptance in widely different cultures indicates that the open and non-didactic format addresses essential and fundamental qualities required for therapeutic engagement and human relatedness. Originality/value: This is the first description of the principles of democratic TCs being applied across different international settings. Its value extends beyond the TC field, to the use of democratic and relational principles' applicability in therapeutic pedagogy and training.